The Importance of Transportation Management in Optimizing Supply Chain Management at Industrial Estate - Sri Sarjana; Nur Khayati; Lis Warini; Pras Wiyati (Puslitbang Transportasi Antarmoda-Kementerian Perhubungan Republik Indonesia, 2020)
Transportation management is able to integrate various components that are highly needed in order to ensure the distribution of goods and services takes place effectively and efficiently. The effects of integrated transportation systems have major contribution to business processes and the sustainability of supply chain system in an area. This study measures role of transportation management, supply chain management, and business performance which carries out business in industrial estate. Survey was conducted on employees working in manufacturing industry in Bekasi region. Analysis technique in this study uses structural equation modeling (SEM). Conclusion obtained from results of analysis states that transportation management has significant influence on supply chain management, and has significant impact on business performance, especially for manufacturing industry. In order to grow and develop and even produce optimal business performance, transportation management support with good, integrated and supported management from various sectors is needed to create superior supply chain management so that transportation management support is needed with good governance, integrated, and supported from various sectors so as to create superior supply chain management so as to ensure the availability of industry needs. Suggestions are recommended in relation to planning of transportation management systems that support needs in industrial estate so as to understand strategies that must be carried out for success of business.